The influence of omeprazole on the dissolution processes of ph-dependent magnetic tablets assessed by pharmacomagnetography - Soares, Guilherme A. [UNESP]; Pires, Deivid W. [UNESP]; Pinto, Leonardo A. [UNESP]; Rodrigues, Gustavo S. [UNESP]; Prospero, André G. [UNESP]; Biasotti, Gabriel G. A. [UNESP]; Bittencourt, Gabriela N. [UNESP]; Stoppa, Erick G. [UNESP]; Corá, Luciana A.; Oliveira, Ricardo B.; Miranda, José R. A. [UNESP] (MDPI, 2021)
Pharmacomagnetography involves the simultaneous assessment of solid dosage forms (SDFs) in the human gastrointestinal (GI) tract and the drug plasmatic concentration, using a biomagnetic technique and pharmacokinetics analysis. This multi-instrumental approach helps the evaluation, as GI variables can interfere with the drug delivery processes. This study aimed to employ pharmacomagnetography to evaluate the influence of omeprazole on the drug release and absorption of metronidazole administered orally in magnetic-coated tablets. Magnetic-coated tablets, coated with Eudragit® E-100 (E100) and containing 100 mg of metronidazole, were produced. For the in vivo experiments, 12 volunteers participated in the two phases of the study (placebo and omeprazole) on different days to assess the bioavailability of metronidazole. The results indicated a shift as the pH of the solution increased and a delay in the dissolution of metronidazole, showing that the pH increase interferes with the release processes of tablets coated with E100. Our study reinforced the advantages of pharmacomagnetography as a tool to perform a multi-instrumental correlation analysis of the disintegration process and the bioavailability of drugs.
Keywords: AC biosusceptometry; Eudragit® E-100; Pharmacomagnetography; Proton pump inhibitor